Μοdeling Environmental Degradation: The Effects of Electricity Consumption, Economic Growth and Globalization - Stamatiou, Pavlos (International Journal of Energy Economics and Policy, 2023)
This study aims to explore the effects of electricity consumption, economic growth and globalization on CO2 emissions in the case of the top ten electricity consuming countries. The sample used is annual data covering the period 1990-2018. This paper adopts the cross-sections independence and controls the heterogeneity between cross-sections by using the second generation econometric of panel data. More precisely, the CIPS unit root test, Pedroni (1999) cointegration, Westerlund (2007) bootstrap cointegration, and FMOLS and DOLS techniques have been applied. Additionally, the Dumitrescu and Hurlin (2012) panel causality test is used to investigate the causal nexus among the examined variables. The findings of the study support that all variables are integrated in the long run. Electricity consumption and economic growth have a positive and significant effect on CO2 emissions in these countries. On the other hand, globalization has a negative and significant effect on CO2 emissions, implying the improvement of environmental quality. The results also support the Environmental Kuznets Curve (EKC), as well as bidirectional causalities between economic growth and CO2 emissions, between electricity consumption and CO2 emissions, and between economic growth and globalization. Furthermore, unidirectional causalities running from globalization to CO2 emissions, from economic growth to electricity consumption, and from electricity consumption to globalization are found. Policy implications are further discussed.